Learning demand and classroom discourse design tools to improve students conceptual understanding of the nature of electrolytes - Ahmad, N. J. (Penerbit Universiti Sains Malaysia, 2019)
This paper reports on two design tools used in a teaching sequence (module) based on the Leeds Model Framework. This model framework draws upon theoretical insights into perspectives on learning and empirical studies to improve the teaching of electrochemistry by using the learning demand and the communicative approach. The learning demand identifies the differences between everyday social language and the school scientific language in terms of both content and the nature of the knowledge that are used to represent the same phenomena. The communicative approach focuses on the classroom discourse, especially on how the teacher interacts with the students when new ideas are introduced on the social plane of the classroom. These two design tools present the fundamental guidelines that could be utilised in designing a teaching sequence to improve students’ conceptual understanding in any specific learning of science content. A study on two intact groups that had similar academic ability was carried out. The experimental class was conducted using the design teaching whilst the baseline group (comparison group) had followed the normal classroom teaching. The students’ conceptual understanding in both classes was tested using a post-diagnostic test. The evaluation of students’ responses of the items in the post diagnostic test was carried out using the ideographic and nomothetic approaches. The results show that there were significant differences in the experimental students’ performances in comparison to the students in the baseline group. The findings suggest that the learning demand and different types of discourses had enabled students to explain some aspects of electrolytic cell content in details. The experimental students had demonstrated better conceptual scientific understanding than the baseline group in the learning area concerning the nature of electrolytes in the electrolytic cell.